Improving the description of solvent pairwise interactions using local solute/solvent three‐body functions. The case of halides and carboxylates in aqueous environment. Issue 11 (31st January 2019) - Réal, Florent; Vallet, Valérie; Masella, Michel
Abstract : We propose a general strategy to remediate force‐field artifacts in describing pairwise interactions among similar molecules M in the vicinity of another chemical species, C, like water molecules interacting at short distance from a monoatomic ion. This strategy is based on introducing a three‐body potential energy term that alters the pairwise interactions among M ‐type molecules when they lie at short range from the species C . In other words the species C is the center of a space domain where the pairwise interactions among the molecules M is altered. Here, we apply it to improve the description of the water interactions provided by the polarizable water model TCPE/2013 in the vicinity of halides, from F − to At −, and of the prototypical carboxylate anion CH3 COO − . We show the accuracy and the transferability of such an approach to investigate not only the hydration process of single anions but also of a salt solution NH 4 + / Cl ‐ in aqueous phase. This strategy can be used to remediate the drawbacks of any kind of force fields. © 2019 Wiley Periodicals, Inc. Abstract : A general strategy is proposed to remediate force‐field artifacts in describing solvent pairwise interactions in the vicinity of a solute, based on introducing a three‐body potential energy term that alters the solvent pairwise interactions in a space domain centered at the solute. It is used to improve the description of the water interactions provided by the polarizable water model TCPE/2013 in the vicinity of halides, from F − to At −, and of the carboxylate anion CH3COO − .